Eosinophilia and Lung Cancer: Analysis From Real-World Data and Mendelian Randomization Study - Wang, Zhufeng; Chen, Bigui; Fu, Yu; Ou, Changxing; Rong, Qiuping; Kong, Xuetao; Xu, Wei; Deng, Yangqing; Jiang, Mei; Xie, Jiaxing (Frontiers in Medicine, 2022)
Background and Objective: Growing evidence added to the results from observational studies of lung cancer patients exhibiting eosinophilia. However, whether eosinophils contributed to tumor immune surveillance or neoplastic evolution was unknown. This study aimed to analyze the causal association between eosinophilia and lung cancer. Methods: Real-world data was collected to describe the clinical characteristics of patients with lung cancer and eosinophilia. Additionally, the causal effect of eosinophil count on lung cancer from a genome-wide association study (GWAS) was investigated using the two-sample Mendelian randomization (MR) method. Secondary results according to different histological subtypes of lung cancer were also implemented. Results: The median absolute eosinophilic count was similar among different histological subtypes of lung cancer [median (min, max): Lung adenocarcinoma 0.7 (0.5, 15); Squamous cell lung cancer 0.7 (0.5, 1.3); Small cell lung cancer 0.7 (0.6, 1.3); p = 0.96]. But the median eosinophil to leukocyte ratio was higher in patients with squamous cell lung cancer [median (min, max): Lung adenocarcinoma 8.7% (2.1%, 42.2%); Squamous cell lung cancer 9.3% (4.1%, 17.7%); Small cell lung cancer 8.9% (5.1%, 24.1%); p = 0.91]. MR methods indicated that eosinophilia could provide 40% higher risk for squamous cell lung cancer in East Asian [MR-Egger: odds ratio (OR) = 1.40, 95% CI: 1.03 – 1.89, p = 0.04]. Conclusion: Our study suggested that eosinophilia was a potential causal risk factor in the progression of squamous cell lung cancer in East Asian.